Regulators of G protein Signaling (RGS) proteins (version 2020.4) in the IUPHAR/BPS Guide to Pharmacology Database. (2020) - Ahlers-Dannen, Katelin E.; Alqinyah, Mohammed; Bodle, Christopher; Dagher, Josephine Bou; Chakravarti, Bandana; Choudhuri, Shreoshi P.; Druey, Kirk M.; Fisher, Rory A.; Gerber, Kyle J.; Hepler, John R.; Hooks, Shelley B.; Kantheti, Havish S.; et al.
No abstract available